Development and Validation of a Simple and Reliable LC-MS/MS Method for the Determination of Acetazolamide, an Effective Carbonic Anhydrase Inhibitor, in Plasma and its Application to a Pharmacokinetic Study - Li, X.; Li, N.; Wang, C.; Deng, S.; Sun, X.; Zhang, W.; Gao, W.; Zhao, D.; Lu, Y.; Chen, X. (Drug Research, 2014)
A simple, rapid and accurate liquid chromatography – tandem mass spectrometry method was developed and validated for the quantification of acetazolamide in beagle plasma using sulfadiazine as the internal standard. After extraction by acetonitrile, the analytes were separated by a rapid gradient elution with acetonitrile and water as the mobile phase on a SHIMADZU VP-ODS C18 column and then detected by an API 4000 triple-quadrupole mass spectrometer using electrospray ionization in negative ion mode. Multiple reaction monitoring was performed on the ion transitions of m/z 220.9→83.3 (acetazolamide) and m/z 248.9→185.0 (sulfadiazine). The plasma concentration of acetazolamide in beagle dogs showed good linearity over the range of 0.20~50 μg/mL, and the intra- and inter-day variations were small with high accuracy and absolute recovery. Both analytes can maintain stable during the whole experimental process. The developed method was successfully applied to the pharmacokinetic study of acetazolamide extended-release capsules after oral administration to beagle dogs.
Keywords: acetazolamide; LC-MS/MS; pharmacokinetics; beagle dogs